Pyrene‐based Schiff Base as Selective Chemosensor for Copper(II) and Sulfide Ions. Issue 23 (20th June 2018) - Dalbera, Subrata; Kulovi, Somnath; Dalai, Sudipta
Abstract: 1‐aminopyrene and 2, 4‐dihydroxy benzaldehyde derived pyrene based chemosensor was obtained by single step synthesis. The sensor is highly selective and sensitive towards Cu 2+ and S 2‐ ions. Sensitivity of the sensor towards Cu 2+ was assessed by UV/Visible absorption and emission spectroscopy while the same for the S 2‐ was colorimetrically assessed. Static quenching mechanism for Cu 2+ was established by time‐resolved fluorescence spectroscopy. Stoichiometry of the sensor with Cu 2+ and S 2‐ ions were found to be 2:2 and 1:1 with the corresponding binding constants as 5.65 ×10 5  M ‐1 and 3.08 ×10 4 M ‐1 . The lower limit of detection of Cu 2+ and S 2‐ by1 is 0.503 and 10 μM respectively projecting the sensor as a potential agent for applications in real samples. Abstract : Effect of Cu 2+ and S 2‐ ions on the emission and absorption of a pyrene based chemosensor.